2019
DOI: 10.3390/ijms20040991
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Neuropathy Affects Cardiac miRNA Expression Network Targeting IGF-1, SLC2a-12, EIF-4e, and ULK-2 mRNAs

Abstract: Background: Here we examined myocardial microRNA (miRNA) expression profile in a sensory neuropathy model with cardiac diastolic dysfunction and aimed to identify key mRNA molecular targets of the differentially expressed miRNAs that may contribute to cardiac dysfunction. Methods: Male Wistar rats were treated with vehicle or capsaicin for 3 days to induce systemic sensory neuropathy. Seven days later, diastolic dysfunction was detected by echocardiography, and miRNAs were isolated from the whole ventricles. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 108 publications
0
20
0
Order By: Relevance
“…It has also been shown that long-term application of insulin modifies the expression of the TRPV1 receptor protein in neuroblastoma cells by regulating the PI3K and MAPK signaling [21]. Additionally, in a recent publication it has been demonstrated, that selective chemodenervation evoked by neonatal capsaicin treatment resulted in changes in myocardial miRNA expression targeting among others the expression network of IGF-1 [81].…”
Section: Effects Of Insulin On Trpv1 Receptor-expressing Nociceptive mentioning
confidence: 99%
“…It has also been shown that long-term application of insulin modifies the expression of the TRPV1 receptor protein in neuroblastoma cells by regulating the PI3K and MAPK signaling [21]. Additionally, in a recent publication it has been demonstrated, that selective chemodenervation evoked by neonatal capsaicin treatment resulted in changes in myocardial miRNA expression targeting among others the expression network of IGF-1 [81].…”
Section: Effects Of Insulin On Trpv1 Receptor-expressing Nociceptive mentioning
confidence: 99%
“…A downstream target of miR-344b is Olig2 [40]. The cardiac expression of miR-344b is affected by sensory neuropathy, but the mechanism is unclear [41]. In our study, we first identified the aberrantly high expression of miR-344b in burn injury-induced cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 83%
“…Recently, we have found an increased end-diastolic diameter, and reduced stroke volume, but maintained EF and FS, after systemic capsaicin-induced sensory desensitization in rats [ 103 ]. Disturbed relaxation was due to reduced basal cardiac NO, superoxide, and peroxynitrite (ONOO − ) formation, and thereby impairment of the physiological S-nitrosylation level of the sarco-endoplasmic reticulum Ca 2+ ATPase 2a (SERCA2a) [ 104 ]. Moreover, we have also investigated the effects of systemic capsaicin-induced sensory neuropathy on cardiac miRNA transcriptomics and shown an altered miRNA expression pattern.…”
Section: The Capsaicin-sensitive Sensory Nerves and The Trpv1 Recementioning
confidence: 99%